(untitled) (Research, Society and Development, 2022)
The aim of this study was to present and discuss the laboratory finding of Fusarium solani as opportunistic agent of invasive mycosis in chicks and eggs on an ostrich farm located in Cosmópolis (São Paulo, Brazil). Dyspnea and tachypnea were the main signs and symptoms presented by the chicks. Multiple whitish foci were found scattered over the chicks’ air sac membranes, lungs and livers and over the external membranes of the eggs. Fungal mycelia were observed in the air compartments of some of the eggs. An isolate purified from a lung culture was subsequently identified as Fusarium solani based on its morphological and molecular profiles. It was likely that the high humidity and temperature, as well as the matte paint that had been applied to the hatchery and birth room walls, provided conditions favoring fungal growth. Strict environmental sanitary measures are necessary to maintain microbial control. Uncommon fungi such as Fusarium solani must be considered as opportunistic pathogens in commercial ostrich culturing.